Formal water rights in rural Tanzania: deepening the dichotomy? - van Koppen, Barbara; Sokile, C.S.; Hatibu, N.; Lankford, B.A.; Mahoo, H.F.; Yanda, P.Z. (International Water Management Institute, 2004)
In the past decade the Tanzanian government, with a loan from the World Bank, designed and implemented a new administrative water rights system with the aim of improving basin-level water management and cost-recovery for government water-resource management services. This paper evaluates the processes and impacts after the first years of implementing the new system in the Upper Ruaha catchment. In this area, the l11<l:iority of water users are small-scale irrigators and livestock keepers who develop and manage water according to customary arrangements, without much state support. Although water resources are abundant, growing water demands intensifY water scarcity during the dry season. Contrary to expectations, the new system has failed as a registration tool, a taxation tool, and a water management tool, and has also contributed to aggravating rural poverty. As a taxation tool, the system not only introduces corruption by design, but also drains government coffers because the collection costs are higher than any revenue gained. As a water management tool, the new system aggravates upstream-do,vnstreanl conflicts, because the upstream water users claim that paying for water entitles them to use it as they like. However, unlike these and other counterproductive impacts of the new system, the taxation of the few private large-scale water users according to negotiated rates appeared to be feasible. The paper argues that the root of these paradoxical results lies in the dichotomy between the 'modern' large-scale rural and urban economy with its corresponding legislation and the rural spheres in which Tanzania's m<l:jority of small-scale water users live under customary water tenure. While the new water rights system fits the relatively better-off minority to some extent, it is an anomaly for Tanzania's majority of poor \yater users. Illis paper concludes by suggesting easy adaptations in the current water rights system that would accommodate both groups ohvater users, improve cost-recovery for government services, mitigate ,vater conflicts and alleviate rural poverty